Evaluation of oenological tannins for preventing the light-struck taste. (15th March 2023) - Fracassetti, Daniela; Messina, Natalia; Saligari, Alberto; Tirelli, Antonio
Highlights: Fifteen commercial tannins were screened for avoiding the light-struck taste (LST). The tannins limited the degradation of methionine. The content of volatile sulfur compounds was up to 10-folds lower with tannins. Flavan-3-ols and tannic acid were related to DMDS and DMTS, and MeSH, under oxic condition. Tannins can be a suitable tool to effectively prevent LST appearance. Abstract: The light-struck taste (LST) is a fault occurring in white and rosé wines associated to the formation of volatile sulfur compounds (VSCs) due to the reactions between riboflavin (RF) and methionine (Met). We investigated the possible preventing effect of 15 commercial tannins of different origin in model wine added with RF and Met, under oxic and anoxic conditions, and submitted to standardized light-exposure. All the tannins limited the degradation of Met in comparison to the tannin-free samples. Lower concentrations of VSCs were found in presence of tannins even under anoxia, condition favouring their formation. The sniffing trials evidenced the minor perception of cooked cabbage note with added tannins. The multivariate analysis showed the presence of flavan-3-ols was related to the formation of DMDS and DMTS, while tannic acid was related to MeSH, both the behaviors occurring under oxic condition. The study highlighted the ability of tannins to prevent the LST.